THE INFLUENCE OF JOB SATISFACTION ON TURNOVER INTENTION OF EVENT WORKERS IN PALEMBANG CITY - Pelliyezer Karo Karo; Muhammad Iqbal Djohan; Meyke Amalia (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
The event sector is synonymous with project-based work, which has no work rhythm, requiring event workers to choose higher endurance than those who work in offices. This study aims to identify the level of job satisfaction concerning the level of perspective on the turnover intention of event workers in Palembang. This quantitative research is in the form of survey research with a total sample of 75 event workers divided into five categories of work scope. The analytical method used is multiple linear regression by identifying the effect of four variables on job satisfaction: financial satisfaction, physical satisfaction, social satisfaction, and psychological satisfaction on turnover intention. The descriptive statistics research results show that three variables fall into the unfavorable category: financial satisfaction, psychological satisfaction, and turnover intention. In contrast, other variables fall into the excellent category. Analysis through inferential statistics shows that all job satisfaction variables influence turnover intention. While partially, two of the four job satisfaction variables, namely physical and psychological satisfaction, impact turnover intention, where psychological satisfaction has the most significant influence value. Judging from the correlation, the dependent variable, job satisfaction, has a strong relationship with the level of turnover intention. In contrast, in terms of determination, job satisfaction impacts 71.1 percent of the turnover intention movement of event workers.